Cognitive developmental change : theories, models and measurement - Demetriou, Andreas; Raftopoulos, Athanassios (Cambridge studies in cognitive perceptual development, 2004)
Makes an original contribution to developmental, cognitive and educational science by bringing together uniquely diverse perspectives for analysing the dynamics of change. Chapters cover key theories of cognitive change, the factors that affect change including neurological, emotional and socio-cultural factors and the latest methods for measuring and modelling change.